EFFECT OF MICROBIAL PHYTASE SUPPLEMENTATION ON GROWTH PERFORMANCE OF JAPANESE QUAILS - Saima; M. A. Shad; T. N. Pasha; M. Akram; Y. A. Ditta; M. Z. U. Khan (Journal of Animal and Plant Sciences, 2014)
A 28 days trial was conducted to evaluate efficacy of microbial phytase in diets for Japanese quails. For this purpose, 900 experimental birds were divided into six groups, each group containing 150 chicks and further sub-divided into10 replicates. Diet A (positive control) was formulated according to NRC (1994) requirements set for the Japanese quail (CP 24% and ME 2900 Kcal/Kg). Diet B differed from diet A in Ca (Calcium) and P (Phosphorus) i.e. 0.15% Ca and 0.20% P less to Diet A, respectively. Four different levels of phytase enzyme (250, 500, 750, 1000 FTU/kg of feed) were added to diet B to formulate diets C, D, E and F treatments respectively. Results revealed that body weight gain, feed consumption, FCR, keel /shank length, dressing percentage of birds in groups consuming 750 and 1000 FTU/kg phytase were significantly higher (P<0.05) than those of B, C and D. The growth performance of group E and F was comparable with those of group A (+ve control). Maximum leg weakness, swollen joints and crippled legs were observed in group B (39.30%) followed by C, D (21.33%,and 16.0%). Keeping in view, performance and mortality rate, it is recommended that microbial phytase may be used with greater confidence in Japanese quail ration.
Keywords: Japanese quail; phytase; growth; dressing percentage